Comparative Study of Extension Mode Method in Reducing Border Distortion Effect for Transient Voltage Disturbance - Saidatul Habsah Asman; Ahmad Farid Abidin (Institute of Advanced Engineering and Science, 2017)
Wavelet transform is an essential method for preprocessing and analyzing non-stationary signal of power quality disturbances. Recently, power quality disturbances cause various effect which reduce the accuracy of the signal such as border distortion. This paper is presenting the comparative study on extension mode scheme to reduce border distortion effect in Discrete Wavelet Transform. The three different method namely zero padding, smooth padding of order 1 and symmetrization mode have been carried to observe their capability on reducing border distortion effectively. The implementation of these modes has been carried out in Matlab Software version R2014a. The analysis is considering the decomposition coefficient at level 4 with mother wavelet type Daubechies. With the aid of soft- threshold function, the noise and unwanted signal is effectively removed to recover the original signal. The comparative study provides the best mode to reduce border distortion effect with the presence of transient voltage is smooth padding of order 1.